Impacts Of Trade Liberalisation On Trade Performance In Bangladesh - Hoque, Mohammad Monjurul (2007)

(untitled)
Experiencing trade imbalances and low GDP growth for long; realising benefits, theoretical and empirical supports to trade liberalisation for trade performance; Bangladesh has been liberalising its trade regime since 1992 for higher trade performance. However, still there is growing concern about its impact on trade performance. Therefore, the general objective of the study is set to evaluate and analyse the impacts of trade liberalisation on trade performance in Bangladesh. The study has developed a theoretical framework in which liberalisation can contribute to trade performance. Empirically, to capture the impacts of liberalisation on trade performance, three trade equations namely import demand, exports supply and trade balance functions for Bangladesh are estimated. Recent econometric methodology, the ARDL ‘Bounds test’ approach to cointegration is applied with annual time series data from 1972-73 to 2004-05 for estimation. Empirical results suggest that the variables in the aggregate import function is cointegrated, and the economy of Bangladesh is quite open in aggregate import.Trade liberalisation dummy impacts positively and import duty impacts negatively on aggregate import. Liberalisation interaction with price decreases import and hence improves trade balance, while interaction with income increases import and hence worsens trade balance. Import duty as a measure of liberalisation impacts negatively higher on import of capital goods compared to others; indicate that Bangladesh is following import liberalisation focused to the import of capital goods. Liberalisation impacts positively on aggregate export. Capital stock as measure of technology transfer does not have any significant impact on aggregate export in the long run. Liberalisation impacts greatly on export of RMG. Capital stock impacts positively on export of RMG while negatively on export of shrimp, jute goods and raw jute; implies that investment is diverting to RMG sector from other areas; which is a reflection of the on-going liberalisation policy pursued by Bangladesh. Reduction of import duty worsens trade deficit in the short run while improves in the long run. Increase in liberalisation, reduction or withdrawal of export duty both contribute to improve trade deficit. Deterioration in the terms of trade worsens trade deficit in the short run, while improves in the long run. Import and trade deficit are largely influenced by increase in income. Therefore, trade liberalisation and other policy options should be fine tuned consistently in line with price stability, increase in absorption and develop backward linkage industries domestically for higher export performance and to improve trade imbalances in Bangladesh.